Molecular cloning, characterization and tissue expression of porcine creatine transporter - ZHANG, ZHONG- YUE; ZUO, JIAN-JUN; DAI, FA-WEN; LEI, JIAN; FENG, DING-YUAN (The Indian Journal of Animal Sciences, 2012)
The present study was to clone porcine creatine transporter from Landrace pig, and investigated its tissue distribution. The full-length cDNA of porcine skeletal muscle creatine transporter (CrT) was first cloned by using rapid amplification of cDNA end technology and the full sequence of porcine skeletal muscle CrT was 2,374bp, with a 1,908bp open reading frame encoding a 635-amino acids protein (a predicted molecular mass of 70.4 kDa). The RT-PCR assay showed that the porcine CrT was highly expressed in porcine skeletal muscle, followed by kidney, lung, heart, liver, brain and spleen. In-situ RT-PCR and enzyme-histochemistry technology were also used to detect the distribution of CrT mRNA in porcine psoas major muscle (PM), the result showed that the area of precipitation was significantly correlated with the area of muscle fibre and the area of type red muscle (ÃŸR) fibre was significantly lower than that of intermediate muscle (aR) or white muscle (aW) types in porcine PM. This is the first systematic report of molecular cloning, characterization and tissue expression of porcine CrT for a better understanding of the creatine metabolism in pigs.